1999
DOI: 10.1295/polymj.31.263
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectric-Like Behavior of Vinylidene Fluoride/Trifluoroethylene Copolymers with Low Vinylidene Fluoride Content

Abstract: ABSTRACT:Yinylidene Fluoride/Trifluoroethylene copolymers with compositions 47/53 and 37/63mol% exhibit a ferroelectric square D-E hysteresis loop at low temperatures (below -40'C) and undergo transition to a paraelectric motional phase near T, = 70"C. At intermediate temperature they exhibit a double-hysteresis loop suggesting that polarization reversal occurs through a non-polar phase. Time domain measurement of polarization reversal shows two-step switching transient consisting of fast depolarization and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…6a) is usually observed in dipole glass [17] and in classical antiferroelectrics; however, it occurs often in polymer ferroelectrics as well [17,32]. Moreover, this shape of the D(E) curve allowed the authors of [33] to claim that antiferroelectricity exists in this class of polymers. This claim should be verified, and, more precisely, we should talk about the apparent similarity because the structural differences between the antifer roelectric crystals and the studied crystallizing poly mers are obvious.…”
Section: Discussionmentioning
confidence: 98%
“…6a) is usually observed in dipole glass [17] and in classical antiferroelectrics; however, it occurs often in polymer ferroelectrics as well [17,32]. Moreover, this shape of the D(E) curve allowed the authors of [33] to claim that antiferroelectricity exists in this class of polymers. This claim should be verified, and, more precisely, we should talk about the apparent similarity because the structural differences between the antifer roelectric crystals and the studied crystallizing poly mers are obvious.…”
Section: Discussionmentioning
confidence: 98%
“…Considering these curve evolution with the decrease of VDF content, polarization hysteresis loops evolve from ferroelectric to antiferroelectric‐like type (Figure 4a), which is accompanied by a remarkable smearing of the butterfly peaks (i.e., VDF = 45 mol%, Figure 4b). The copolymers with antiferroelectric‐like loops (VDF < 49 mol%) are not in a true antiferroelectric phase due to the absence of typical strain response characteristic of antiferroelectric materials (Figure 4b). In addition, Figure 4b shows that the emergence of relaxor behavior for VDF ≤ 55 mol% largely improves the strain response, as relaxor ferroelectrics are known to exhibit remarkably larger electrostriction strain than normal ferroelectrics …”
Section: Origin and Tuning Of Negative Longitudinal Piezoelectric Coementioning
confidence: 99%
“…In the range of 30-50 mol% VDF content, copolymers exhibit a double hysteresis loop at room temperature, implying that polarization reversal occurs through a nonpolar state. [4][5][6] It has been shown that the double loop is converted into a ferroelectric square loop as the temperature is decreased. At high temperatures, they undergo transition to a paraelectric motional phase.…”
Section: Introductionmentioning
confidence: 99%